PENGARUH LEVERAGE, LIKUIDITAS, DAN KEPEMILIKAN INSTITUSIONAL TERHAHAP KUALITAS LAPORAN KEUANGAN PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Priskila Georgina Verene; Y. Agus Bagus Budi N (STMIK Widuri Jakarta, 2024)
The aim of this research is to identify the influence of leverage, liquidity and institutional ownership on the quality of financial reports. The population in this research is 26 food and beverage manufacturing industries listed on the Indonesian Impact Exchange in 2018-2022. The type of information used in this research is quantitative information. The source of information used in this research is secondary information. The illustration collection method used purposive sampling and the illustrations used were 20 companies. The information analysis research method used in this research is panel information regression. The research results show that leverage has no influence, on the contrary, liquidity and institutional ownership have a positive and significant influence on the quality of financial reports in the food and beverage subsector manufacturing industry listed on the Indonesian Impact Exchange in 2018-2022.